Efficacy and Safety of Re Du Ning Injection for Acute Exacerbations of Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis. (21st March 2022) - Shu, Bofei; Li, Hong; Zhou, Xu; Ding, Zhaohui; Wan, Liling
Abstract : Background . Re Du Ning, a traditional Chinese medicine injection, has been widely used for the treatment of chronic obstructive pulmonary disease, although without established systematic review evidence. This systematic review aimed to assess the efficacy and safety of Re Du Ning in the treatment of acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Methods . We searched seven databases (PubMed, Embase, the Cochrane Library, SinoMed, CNKI, WanFang, and the Chinese Clinical Trial Registry) up to November 1, 2021, to identify randomized controlled trials of Re Du Ning for AECOPD. Two researchers independently carried out literature screening and data extraction. Effects were measured by risk ratios (RRs) or mean differences (MDs) with 95% confidence intervals (CIs). The meta-analysis was completed by RevMan 5.4 software. Results . Twenty-six studies met the eligibility criteria, with a total of 2284 patients. The findings of the meta-analysis indicated that the response rate of the experimental group was higher than that of the control group: RR = 1.14% and 95% CI: (1.09, 1.19). Significantly greater improvements in pulmonary function: FEV1: MD = 0.28 L, 95% CI: (0.20, 0.36); FEV1/FVC: MD = 8.63%, 95% CI: (4.68, 12.59); T-lymphocyte counts: CD4: MD = 6%, 95% CI: (2.44, 9.56); CD3: MD = 10.42%, 95% CI: (8.6, 12.24); CD4/CD8: MD = 0.38%, 95% CI: (0.32, 0.43); acid/base imbalance: PH: MD = 0.05, 95% CI: (0.01, 0.10); PaO2: MD = 9.02 mmHg, 95% CI: (11.11, 0.10), p = 0.005 ; C-reactive protein: MD = −6.65 mg/L, 95% CI: (−10.97, −2.34); and PCT: MD = −0.28 μ g/L, 95% (CI: −0.41, −0.15) were observed in patients receiving Re Du Ning compared with those receiving the control treatment. Re Du Ning did not significantly change the carbon dioxide partial pressure. All reported adverse reactions were mild. Conclusion . Re Du Ning injection, as a complementary therapy to routine treatment, has better efficacy than Western medicine alone in relieving clinical symptoms, delaying pulmonary function decline, and improving inflammation indicators for AECOPD, with good safety. The evidence was limited by a lack of high-quality RCTs.